Penyelesaian Sengketa Non-Performing Loan Melalui Mediasi Dalam Sistem Peradilan Perdata (Eksekusi Jaminan Hak Tanggungan) (Jurnal Hukum Magnum Opus, 2023)
This research talks about the implementation and barriers of non-performing loan dispute resolution by executing the object of collateral rights through mediation in the Indonesian Civil Justice System. The research method used is normative legal research and descriptive analysis. The results of this study are the implementation of non-performing loan dispute resolution through mediation in the civil justice system by executing mortgage collateral objects has identified of dualism process namely the integration of the mediation process into the litigation process, even though the mediation process can be carried out when resolving disputes in the non-litigation realm. Then, there are barriers to non-performing loan dispute resolution by executing the object of collateral rights through mediation in the Indonesian Civil Justice System, first, because of the parties factor; second, legal substance factor; third, legal apparatus; and fourth, processes dualism. There are dualism processes in the procedural law of the Indonesian civil justice system that must be taken by the parties has hampered the implementation of the process of executing the mortgage object guarantee (through an auction) as an attempt to resolve non-performing loan disputes through mediation in the civil justice system. So, the that's dualism process makes the execution process late, resulting in losses for the creditor (because of the cessation of financial circulation) and the debtor (because they have to bear interest and fines). Keywords: civil justice system; dispute resolution (meditation); non-performing loan Abstrak Penelitian ini untuk mengetahui pelaksanaan dan hambatan penyelesaian sengketa non-performing loan dengan melakukan eksekusi jaminan hak tanggungan (hak atas tanah) secara mediasi dalam sistem peradilan perdata Indonesia. Metode penelitian yang digunakan ialah penelitian hukum normatif dan deskriptif analisis. Hasil penelitian ini ialah pelaksanaan penyelesaian sengketa non-performing loan melalui mediasi dalam sistem peradilan perdata dengan melakukan eksekusi benda jaminan hak tanggungan (hak atas tanah) telah teridentifikasi adanya “dualisme proses” yaitu adanya pengintegrasian proses mediasi ke dalam proses beracara di ranah litigasi, padahal proses mediasi dapat dilakukan para pihak ketika hendak menyelesaikan sengketa pada ranah non litigasi. Kemudian terdapat beberapa faktor penghambat yang menyebabkan penyelesaian sengketa non-performing loan melalui mediasi dalam sistem peradilan perdata, yaitu pertama, faktor para pihak; kedua, faktor substansi hukum; ketiga, faktor aparatur hukum; dan keempat adanya dualisme proses dalam hukum acara sistem peradilan perdata Indonesia yang harus ditempuh para pihak telah menghambat pelaksanaan proses eksekusi objek jaminan hak tanggungan (melalui pelelangan umum), sebagai upaya untuk menyelesaikan sengketa non-performing loan melalui mediasi di dalam sistem peradilan perdata. Dalam artian dualisme proses itu membuat proses eksekusi terlambat dilaksanakan, sehingga mengakibatkan kerugian bagi kreditur (karena terhentinya perputaran keuangan) dan debitur (karena harus menanggung beban bunga dan denda). Kata kunci: non-performing loan; penyelesaian sengketa (mediasi); sistem peradilan perdata